ANALISIS PENGARUH RETURN ON ASSETS DAN CURRENT RATIO TERHADAP DIVIDEND PAYOUT RATIO DENGAN EFFECTIVE TAX RATE SEBAGAI VARIABEL MEDIASI (Studi pada Perusahaan Farmasi di Bursa Efek Indonesia) - Elyasa Ramadhany; Adya Hermawati; Gunarianto, Gunarianto (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The aim of this research is to obtain empirical evidence of the influence of ROA (return on assets) and CR (current ratio) on DPR (dividend payout ratio), both directly and through the mediation of ETR (effective tax rate). This type of research is quantitative with the SEM-SmartPLS method. Data was obtained from 11 pharmaceutical companies listed on the BEI (Indonesian Stock Exchange) for the period 2019, 2020, 2021, 2022 and 2023. Based on the criteria determined by the researchers (purposive sampling), the sample for this study consisted of 11 pharmaceutical companies. The empirical evidence obtained is that there is a significant direct influence of ROA (return on assets) and CR (current ratio) on DPR (dividend payout ratio). However, no indirect effect was found through ETR (effective tax rate) mediation. So, ETR (effective tax rate) did not succeed in being a strong mediator of the influence of the two variables ROA (return on assets) and CR (current ratio) on DPR (dividend payout ratio). One of the reasons is that there is no significant influence of the ETR (effective tax rate) on the DPR (dividend payout ratio). Tax incentives provided by the government for companies listed on the Indonesia Stock Exchange are able to encourage management to focus more on company performance